Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1021/acsnano.5b06074
|View full text |Cite
|
Sign up to set email alerts
|

Inkjet Color Printing by Interference Nanostructures

Abstract: Color printing technology is developing rapidly; in less than 40 years, it moved from dot matrix printers with an ink-soaked cloth ribbon to 3D printers used to make three-dimensional color objects. Nevertheless, what remained unchanged over this time is the fact that in each case, dye inks (CMYK or RGB color schemes) were exclusively used for coloring, which inevitably limits the technological possibilities and color reproduction. As a next step in printing color images and storing information, we propose the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
69
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 84 publications
(71 citation statements)
references
References 37 publications
1
69
0
1
Order By: Relevance
“…To produce basic optical components by inkjet printing, we use titania-based inks [8]. A distinctive feature of most sol-gel inks is the ability to adjust viscosity and surface tension by diluting with alcohols [30].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To produce basic optical components by inkjet printing, we use titania-based inks [8]. A distinctive feature of most sol-gel inks is the ability to adjust viscosity and surface tension by diluting with alcohols [30].…”
Section: Resultsmentioning
confidence: 99%
“…Previously inkjet printing has been applied for producing various coatings ranging from conductive transparent films to optical coatings [6]. The development of nanoparticle-based inks allowed expanding [7] the applicability of inkjet printing to fabrication of micro and nanostructured solid objects with a resolution of up to 20 nm along the z-axis [8]. This technological advancement was the result of the unique properties of nanoparticles related to both their small dimensions and specific physico-chemical characteristics, which allow producing uniform layers [9] and induce self-assembly of materials [10] and specific packing on the surface of substrates giving rise to important properties of the resulting materials including new optical characteristics inaccessible to the respective bulk materials.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Techniques based on inkjet printing of functional inks have been extensively discussed in the recent literature as practical approaches to directly pattern various classes of materials on supports for applications in electronics, 1,2 micromechanics, 3 biomedicine 4 and other areas. [5][6][7] In our previous studies, we have reported the development of functional inorganic inks for inkjet printing of well-defined heterostructures suitable for applications such as color interference images 8 and masking rainbow holograms. 9 Conventionally, the spatial resolution in inkjet printing of functional materials is limited to 10-20 mm as determined by a combination of factors such as the droplet diameters, placement errors and physicochemical characteristics of the inks.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the interference spectrum, the refractive index of the films was calculated according to an example shown in ref. 8.…”
mentioning
confidence: 99%